2015
DOI: 10.1159/000371673
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acids and Stellate Cells

Abstract: Hepatic stellate cells are mainly known for their contribution to fibrogenesis in chronic liver diseases, but their identity and function in normal liver remain unclear. They were recently identified as liver-resident mesenchymal stem cells (MSCs), which can differentiate not only into adipocytes and osteocytes, but also into liver epithelial cells such as hepatocytes and bile duct cells as investigated in vitro and in vivo. During hepatic differentiation, stellate cells and other MSCs transiently develop into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Regarding the degree of involvement of BAs in organs, excluding the liver, G protein-coupled receptor (TGR5) was reported as membrane-type BA receptor that is activated by BAs in the order of LCA > DCA > CDCA > CA in intestinal neuroendocrine cells, as well as the gall bladder, spleen, brown adipose tissue, macrophages, and cholangiocytes [ 40 , 41 ]. Therefore, BAs are pivotal signaling molecules stimulating FXR or TGR5 in many organs [ 15 , 42 , 43 , 44 , 45 , 46 , 47 ]. Additionally, HSCs activated in response to liver injury express TLR4, which promotes the activation of IκB kinase/NF-κB and JNK pathways in addition to the secretion of IL-6, transforming growth factor-β (TGF-β1), and monocyte chemoattractant protein 1 (MCP-1) [ 48 ]; however, it is unclear how these processes can be inhibited, which requires future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the degree of involvement of BAs in organs, excluding the liver, G protein-coupled receptor (TGR5) was reported as membrane-type BA receptor that is activated by BAs in the order of LCA > DCA > CDCA > CA in intestinal neuroendocrine cells, as well as the gall bladder, spleen, brown adipose tissue, macrophages, and cholangiocytes [ 40 , 41 ]. Therefore, BAs are pivotal signaling molecules stimulating FXR or TGR5 in many organs [ 15 , 42 , 43 , 44 , 45 , 46 , 47 ]. Additionally, HSCs activated in response to liver injury express TLR4, which promotes the activation of IκB kinase/NF-κB and JNK pathways in addition to the secretion of IL-6, transforming growth factor-β (TGF-β1), and monocyte chemoattractant protein 1 (MCP-1) [ 48 ]; however, it is unclear how these processes can be inhibited, which requires future studies.…”
Section: Discussionmentioning
confidence: 99%
“…TGR5 (Gpbar1) is a G protein-coupled bile acid receptor expressed in various cell types, including macrophages, as well as non-parenchymal liver cells such as activated hepatic stellate cells (HSCs) and liver sinusoidal endothelial cells (LSECs) [1,2,3,4,5]. Activation of TGR5 occurs after binding of bile acids (BAs), leading to an intracellular increase of cyclic AMP (cAMP) as second messenger and to the activation of further downstream signaling [6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of this include the differentiation of liver progenitor cells (LPCs) into hepatocytes or cholangiocytes, as well as the differentiation of hepatocytes and cholangiocytes into LPCs, and the trans-differentiation between hepatocytes and cholangiocytes (Ko et al, 2020;Li et al, 2020;So et al, 2020). It has also been observed that HSCs show mesenchymal stem cell properties and can also give rise to hepatocytes and cholangiocytes (Kordes et al, 2015;Kordes et al, 2021). In addition, hepatocytes can undergo partial EMT during liver regeneration (Oh et al, 2018).…”
Section: Physiological Context Of the Livermentioning
confidence: 99%